Evaluasi Kegiatan KKG PAI Dalam Menghasilkan Butir Tes Objektif Menggunakan Model CIPP - Vira Rahmadianti; Arifmiboy Arifmiboy; Junaidi Junaidi; Hamdi Abdul Karim (Universitas Pahlawan Tuanku Tambusai, 2024)
This research was motivated by PAI KKG activities in producing objective test items in Malalak sub-district. The KKG activity has been running for quite a long time but has never been evaluated, so it cannot be known for certain whether the activity has achieved its objectives or not. To find out the level of success of this PAI KKG activity, the author wants to carry out an evaluation using the CIPP model. This research uses a type of evaluation research with the CIPP model. The population of this research is PAI teachers in Malalak sub-district and the sample of this research is members of the PAI KKG in Malalak sub-district. The data collection process was carried out through questionnaires, interviews and documentation. Then it is processed using simple statistics, namely only looking for achievement d with a value range of 0-100. processed using simple statistics, namely only looking for achievements with a value range of 0-100. The results of this research are summarized as follows: the evaluation of PAI KKG activities in terms of context has an achievement value of 17 with very poor interpretation, input has an achievement value of 71 with good interpretation, process has an achievement value of 85 with very good interpretation and product has an achievement value of 100 with very good interpretation. Good.